A prospective study of the effectiveness of electronic patient records in rapid-cycle assessment of treatment and partner notification outcomes for patients with genital chlamydia and gonorrhoea infection. Issue 2 (8th November 2010) - Brook, M Gary; Rusere, Lovemore; Coppin-Browne, Lizz; McDonagh, Stephanie; McSorley, John
Abstract : Objective: To assess the effectiveness of electronic patient records (EPRs) in facilitating multiple, rapid measurements of treatment and partner notification (PN) outcomes for chlamydia and gonorrhoea. Methods: In two sexual health clinics, the proportion of patients with chlamydia and gonorrhoea who had been treated within 4 weeks of diagnosis was measured, and also the proportion where at least one of their partners had been treated. These outcomes were measured monthly for 6 months, and changes in recording practice were instituted when necessary. Results: It took 8 h to capture and analyse the data for 89 patients in month 1. The health advisers subsequently entered data into searchable fields to facilitate better data capture. As a result, by month 6 it took only 1.5 h to measure these outcomes using an electronic search. It had previously taken 2 days to perform the same analysis using paper records. In month 1, successful treatment was recorded in 26/27 (96%) patients with gonorrhoea and 57/61 (93%) with chlamydia, and there was successful PN for gonorrhoea and chlamydia patients in 19/27 (70%) and 39/61 (64%). By month 6, the recorded outcomes were 30/31 (97%) and 81/86 (94%), respectively, for successful treatment and 28/31 (90%) and 74/86 (86%) for successful PN, respectively. Conclusions: Frequent rapid clinical outcome monitoring is easily attained using EPRs as long as the data are entered into searchable fields. Treatment and PN success for chlamydia and gonorrhoea with this method are well above national targets, which may be attributable to both the use of EPRs and better data capture.